MyBrain15: implementation success for knowledge economy: the influential factors / Assoc. Prof. Dr. Nik Maheran Nik Muhammad ... [et al.] - Nik Muhammad, Nik Maheran; Abd. Rahman, Kahartini; Ng, Siew Foen; Ismail, Nurazleena (2010)
Production of PhD graduates is of vital importance for new knowledge economy in Malaysia. Its core idea is that future economic performance will be closely based on the skill and innovation level of the labor force, underpinned by effective research and R&D capacity. Concern over the potential shortages of doctorates in Malaysian workforce, Malaysia's Action Plan to increase numbers of doctorates within the next 15 years has led to the brainchild of the programme named MyBrain15. MyBrain15 was initiated in the year of 2009 aimed to increase the national competency and capacity for higher level research and innovation by increasing the number of doctorate holders from 8,000 in year 2009 to 60,000 in 2023 (an increment of 8 to 12 percent per year).